If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 4 = -2 Reorder the terms: 4 + 2y = -2 Solving 4 + 2y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2y = -2 + -4 Combine like terms: 4 + -4 = 0 0 + 2y = -2 + -4 2y = -2 + -4 Combine like terms: -2 + -4 = -6 2y = -6 Divide each side by '2'. y = -3 Simplifying y = -3
| 13=4m+7-m | | 7n-4+8n-3= | | 4.4q-3.7-5.5q=-0.1q-3.7 | | -19=5v+6 | | 0.08(y-8)+0.14y=0.18y-1 | | -14=-2+3v | | 6(6v+6)-5-6v=1 | | 5(x+6)=3(x+10)+2x | | (4x-4)+(3x+12)=0 | | 4x+x-6=5 | | 58=4x+10 | | -7(v+4)+4v+5=5v+11 | | 2(5r-9)= | | -3c-5-2c+6= | | 21x-11-12x=3(3x+5)+4 | | 1/9=5/3x | | (68-32)5/9 | | 8n-17n=18 | | 9x^2-11x-114=0 | | 8=3y-13 | | 2x-6=8x-14 | | 7x-1-6x=0 | | 7+(6-8p)-9=0 | | 167=82-x | | 194-u=270 | | 5y+16=3y-8 | | sin(4x)=sin(x) | | 4.8t-2=3.8t-2 | | 14-u=218 | | (1/x)+(1/x+2)=(1/5) | | 6xy+6xy= | | 8w+2-4w=6+w-10 |